Analysis of sleep quality and quantity during a half-season in world-class handball players - Font, Roger; Ortega-Becerra, Manuel; Tremps, Víctor; Vicente, Antoni; Merayo, Ana; Mallol, Milos (Biology of Sport, 2025)
The study aimed to analyse the quality of rest of elite handball players during a half-season and to examine the differences between home and away rest. Adequate rest is key to recovery and performance, but the high density of matches and travel may affect sleep quality and duration. A longitudinal study was conducted over 14 weeks during the 2020–2021 season using sleep monitoring rings in 13 elite handball players to measure physiological and sleep parameters. The variables were compared in different situations such as after a training session, home and away matches, and periods with their national teams. Oura rings were used to collect variables such as heart rate variability, respiratory rate, sleep duration, onset latency and efficiency. Players wore the rings daily excluding training and matches. The data were analysed by comparing the different variablesstudied. At the physiological level, there were no significant differences between situations. However, moderate differences were found in total time in bed between home matches and travel days (ES = 0.57). There was also less sleep time after matches and travel. Players demonstrated good autonomic flexibility without physiological alterations. However, recovery strategiesshould be improved asrest time was not adequate after matches and travel. Individual profiles could help detect recovery deficits.